How Many Cases of Spine Surgery Are Performed in Germany? Method of Counting the Number of Cases of Spine Surgery in Germany - Wieser, Lea-Marie; Sauermann, Sven; Weber, Friedrich (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2016)
Objective The number of cases of spinal DRGs (German Diagnosis-Related Groups) is calculated on the basis of the data released by the German DRG-Institute. The data thus obtained were subsequently compared with the previously publicly debated data of cases, which were based on the counting of OPS (German Procedure Classification) codes.Methods Specific and Nonspecific Spinal DRGs are identified according to the German Coding Guidelines and the OPS catalogs. Those are verified in a multistage process, including the formation of test cases, to ensure that those DRGs consistently contain spinal cases. The verified DRGs are filtered out of the G-DRG § 21 KHEntgG Browser, including the years from 2005 to 2012 to calculate the respective number of cases. For a better overview, the DRGs are divided into groups according to Specific and Nonspecific Spinal DRGs. Both groups are summarized under the title Surgical Spine DRGs to be able to compare the results with the data already published. Two datasets are used for comparison: one from a publication in the German Ärzteblatt, which is based on the data collected by the German insurance company AOK, and the other from data published by the German Federal Office of Statistics.Results As a result, the number of cases which is presented here shows a significant variance compared with the figures that have been published. The Specific Spinal DRGs show a growth of 75% from 2005 to 2011. The case numbers of the Nonspecific Spinal DRGs show an increased rate of 51% between 2005 and 2006. In addition, the Surgical Spine DRGs rose by 69% between 2005 and 2011. This contrasts with the German government-proposed increase of 125% in the area of spinal surgery over the same period.Conclusion To summarize, the significant gap between the case numbers presented here and the existing ones gives reason to question the benefit of using OPS codes to calculate the actual number of cases in the field of spinal surgery, and it suggests the advantage of using DRG-based calculations.
Keywords: spine; increase in case numbers; surgery; Diagnosis-Related Groups; German Procedure Classification (OPS)